ECONOMIC DETERMINANTS OF DIVORCE IN KUDUS REGENCY: A SOCIO-JURIDICAL ANALYSIS OF ISLAMIC FAMILY LAW - Izzul Mutho`; Abdul Rozak; Muhammad Rizal Khoirul Umam3 (USRAH: Jurnal Hukum Keluarga Islam, 2026)
Divorce cases in Kudus Regency show a worrying upward trend, primarily driven by economic factors. Economic hardship contributes significantly to the annual increase in divorce cases. This study examines the high divorce rate in Kudus Regency with a specific focus on analyzing economic factors as the main determinant. This research employs a qualitative field study method with a socio-juridical approach, collecting data through interviews, observations, and analysis of case documents at the Kudus Religious Court. The findings delineate two categories of economic causes: internal factors (husband's failure to provide support, debt burden, and wife's excessive demands) and external factors (slowdown in the raw material processing industry leading to unemployment and unstable income). The study concludes that economic factors are a critical determinant of divorce in Kudus. The findings contribute significantly to the discourse of Islamic family law by proposing that strengthening household economic resilience is a crucial policy recommendation for divorce prevention.